TINDAK TUTUR DIREKTIF GURU DI SLB TUNAS KASIH SURABAYA (KAJIAN PRAGMATIK) - Oktaviary, Halimatus; Turistiani, Trinil Dwi; ., Suhartono (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Pattimura (Indonesia Language and Literature Education Department, The Faculty of Teacher's Training and Educational Sciences, University of Pattimura), 2024)
Abstract: This study aims to describe directive speech acts and teacher speaking strategies at SLB Tunas Kasih Surabaya. The study uses a qualitative descriptive approach with data in the form of speech containing directive speech acts and teacher speaking strategies. Data collection was carried out using the STLC (Listening Without Speaking) method by recording teacher conversations in class. Data analysis used the Miles & Huberman method through 3 steps, namely data reduction, presentation, and verification conclusions. The findings of the study in the form of teacher speech acts amounted to 209 data consisting of commanding speech (75), requesting (34), advising (43), challenging (31), and recommending (24). In addition, 157 teacher speaking strategies were also found consisting of strategies for speaking frankly without further ado (99), speaking with positive politeness (54), and speaking with negative politeness (4). Keywords: Directive Speech, Speech Strategies, Pragmatic